Determination of damage in transparent optically active materials by using polarized light and the Sobel operator - Silvija Galić; Dubravka Špiranović-Kanižaj; Alfonzo Baumgartner (International Journal of Electrical and Computer Engineering Systems, 2012)
This study deals with determination of the percentage of damage in an optically active, translucent material (polystyrene). We made cracks visible by placing the material into the polariscope (between the polarizer and analyzer), and the numerical value of damage was determined by using Sobel, one of the Matlab’s operators for edge detection.